Analysis and assessment of the impact of transport corridor construction on the regional economic development of mountainous areas in southern Bulgaria: A case study - Tsonkov, Nikolay; Petrov, Kamen (Journal of Asian Scientific Research, 2025)
In the Balkan region of Southeastern Europe, many rural, mountainous, and cross-border areas are situated. These areas are isolated from central regions, have low connectivity, and are socioeconomically underdeveloped. At the same time, there is a notable lack of research in the scientific literature on accessibility and regional policies. This article examines the potential for developing a parallel transport corridor in southern Bulgaria, situated in the cross-border region that encompasses Bulgaria, Greece, and Turkey. The authors consider the new transport route as a means of enhancing regional connectivity, thereby promoting economic and social integration within the area. The authors study the region’s potential trajectory and assess the capacity of infrastructural elements for promoting regional development. A research approach is proposed to demonstrate the direct correlation between road network density and regional economic development. The authors employ an interdisciplinary approach to assess and analyze the impact of road infrastructure on the development of mountain areas in Bulgaria. Infrastructure has a significant effect on improving the connectivity and accessibility of Bulgaria’s mountainous regions, thereby stimulating regional development. The study examines the relationship between the development of the road network in Bulgaria and regional economic development.